A Response to Calls for SEC-Mandated ESG Disclosure - Amanda M. Rose (Washington University Law Review, 2021)
This Article responds to recent proposals calling for the SEC to adopt a mandatory ESG-disclosure framework. It illustrates how the breadth and vagueness of these proposals obscures the important—and controversial—policy questions that would need to be addressed before the SEC could move forward on the proposals in a principled way. The questions raised include some of the most contested in the field of corporate and securities law, such as the value of interjurisdictional competition for corporate charters, the right way to conceptualize the purpose of the corporation, the proper allocation of managerial power as between the board and shareholders, and the social desirability of fraud-on-the-market class actions.
Keywords: ESG Disclosure; Corporate law; Securities law; Corporate purpose; SEC filing requirements; Corporate governance